Perceraian dalam Al-Qur’an dan Al-Kitab: Pendekatan Intertekstualitas Julia Kristeva - Kusuma, Juwanda Adi (Jurnal Penelitian Ilmu Ushuluddin, 2024)
This article focuses on analyzing the portrayal of divorce in the Quran and the Bible. The researcher is intrigued by comparing these two sacred texts due to the similarities and differences in how they address divorce. In this study, the intertextuality theory by Julia Kristeva is employed as an analytical tool to examine the topic of divorce in both texts. The research findings indicate that the Sharia laws in the Quran appear proportional and comprehensive, suggesting that divorce can be a last resort if efforts to maintain the marriage are futile. On the other hand, in the Bible, the existing rules are unclear, and from the textual guiding verses, there is no concept of divorce at all. This creates an internal issue within the Christian community.